Vascular Smooth Muscle FTO Promotes Aortic Dissecting Aneurysms via m6A Modification of Klf5 - Ma, Dong; Liu, Xiao; Zhang, Jin-jin; Zhao, Jun-jian; Xiong, Yan-jie; Chang, Quan; Wang, Hong-yan; Su, Peng; Meng, Jia; Zhao, Yong-bo (Frontiers in Cardiovascular Medicine, 2020)
Background: Aortic dissecting aneurysm (ADA) represents an aortic remodeling disease with a high mortality rate. Fat mass and obesity-associated protein (FTO) exerts RNA demethylation function to regulate gene expression related to stem cell differentiation, DNA damage repair, and tumorigenesis, but the role of FTO in ADA is still unclear. Methods: The expression and location of FTO in 43 ADA tissues and 11 normal tissues were determined by RT-qPCR, WB, immunohistochemistry, and immunofluorescence staining. Detecting proliferation and migration of VSMCs. M6A methylated RNA immuno-precipitation qRT-PCR and dual luciferase reporter assay were performed for determining m6A level and interaction between m6A modulation and Klf5 mRNA, respectively. Results: FTO are highly expressed in VSMCs. FTO was positively correlated with BMI, triglyceride, and D-dimer (all P < 0.05). Functionally, both AngII-induced FTO expression and over expression of FTO promote cell proliferation and migration, whereas knockdown of FTO inhibits these functions. Mechanically, we identified Krüppel-like factor 5 (Klf5) as a target of FTO mediating m6A modification. Overexpression of FTO reduced m6A modification on Klf5 mRNA and promoted Klf5 mRNA expression. Furthermore, the p-GSK3β and Klf5 levels increased after FTO overexpression. Finally, knockdown of FTO suppresses the p-GSK3β levels and Klf5 expression regardless of AngII treatment. Conclusions: Our study revealed that FTO expression significantly contributes to the phenotype conversion of VSMCs and the ADA by the demethylation function (m6A), thereby providing a novel therapeutic target.